Routine rhesus-D genotyping in amniotic fluid: analysis of exon 10 versus intron 4 by polymerase chain reaction - Müller, Thomas; Lammers, I.; Gran, S.; Neuse, I.; Leo, Albrecht; Schunter, F. (Beiträge zur Infusionstherapie und Transfusionsmedizin, 1997)
Both the exon 10 and the intron between exons 4 and 5 of the Rh-D gene were analyzed in DNA from amniotic cells by polymerase chain reaction (PCR) in order to determine the fetal Rh-D status. Residual (0.3-2 ml) samples of amniotic fluid obtained by diagnostic amniocentesis in Rh-D-negative women were analyzed. It is important to standardize the sampling and preanalytical storage and to optimize DNA extraction procedures as well as the detection of PCR products for maximal sensitivity. Genotyping was successful in approximately 90% (229 of 256) of amniotic fluid samples tested. Consistent Rh-D results were obtained by both methods in all 229 typed samples with a single exception. Our experience demonstrates that routine genotyping of the Rh-D blood group in small volumes of amniotic fluid (0.5-2 ml) is feasible. Its validity is currently tested by comparison of the prenatal genotype with the serotype of the newborn.